ANALISIS SOLVABILITAS, UKURAN PERUSAHAAN, OPINI AUDIT, TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Silitonga, Friska; Br.Purba , Neni Marlina (SCIENTIA JOURNAL, 2022)
This study aims to determine the effect of solvency, firm size, audit opinion, on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange in the last 5 years, 2016-2020. The population in this study are all manufacturing companies in the goods and consumption sector listed on the Indonesia Stock Exchange in the last 5 years, 2016-2020. This study uses a technique in determining the sample, namely the perposive sampling technique. There are 28 companies as samples and 140 data to be processed. The data collection method was obtained by the documentation method from the information on the financial statements of companies listed on the Indonesia Stock Exchange. While the data analysis method is descriptive statistical method, classical assumption test, and multiple linear regression analysis. The results of the T test analysis prove that Solvency has a negative effect on Audit Report lag, Company Size has a negative effect on Audit Report Lag, audit Opinion has no effect on audit report lag. Simultaneously the effect of Solvency, Firm Size and Audit Opinion on the audit Report Lag has a significant value on the audit Report Lag.